Penggunaan Kosakata Ciptaan Roald Dahl Sebagai Ide Penciptaan Karya Seni Lukis - Kurniawan, Naja Izzah; Wicaksono, Satrio Hari; Junaedi, Deni (Institut Seni Indonesia Yogyakarta, 2024)
Painting is a visual language that can be the means of expressing one's creative expression and is useful in improving one's ability to think and imagine, especially one's aesthetic sensitivity. The transfer of language from verbal language to visual language is carried out in this Final Project by adopting the use of unique vocabulary found in Roald Dahl's children's novels in the form of paintings.‘Gobblefunk’ is a term created by Dahl to describe his own language. In this Final Project, his gobblefunk vocabulary is interpreted and used in the title of the work which has personal tendencies before being realized as a painting. The hope of achieving this Final Project is to represent the use of vocabulary created by Roald Dahl and the world of fantasy contained in his writings. This is channeled through a series of works that have a surrealistic component, colours that give a fantasy feel, human figures, and/or man-made or natural objects/subjects that are integrated into watercolour paintings with the addition of other media. Seni lukis merupakan salah satu bahasa imaji yang mampu menjadi sarana dalam mengeluarkan ekspresi kreatif seseorang dan bermanfaat dalam mengasah kemampuan berpikir dan berimajinasi, ataupun kepekaan estetika seseorang. Alih wahana dari bahasa verbal menjadi bahasa imaji dilakukan dalam Tugas Akhir ini dengan mengangkat penggunaan kosakata unik yang ditemukan dalam novel anak ciptaan Roald Dahl ke dalam wujud karya seni lukis. ‘Gobblefunk’ merupakan istilah yang dibuat oleh Roald Dahl untuk menyebut bahasa ciptaannya sendiri. Dalam Tugas Akhir ini, kosakata gobblefunk ciptaan Roald Dahl diinterpretasi dan digunakan dalam judul karya yang bersifat personal sebelum diwujudkan sebagai lukisan. Harapan capaian dari Tugas Akhir ini untuk merepresentasikan penggunaan kosakata ciptaan Roald Dahl dan dunia fantasi yang terdapat dalam tulisan-tulisannya. Hal tersebut disalurkan melalui rangkain karya yang memiliki komponen surealistik, warna yang memberikan nuansa fantasi, figur manusia, dan atau objek/subjek buatan manusia maupun alami yang terpadukan dalam lukisan cat air dengan tambahan media lain.